Animal Models and Pathogenesis on Neurodegenerative Disorders (Huntington’s Disease): An Updated Review - Diwakar, Diksha; Khan, Shahbaz; lodha, Shivani; Pal, Deepika; Kumar, Dinesh; Kumar, Devesh; Lohani, Alka (Indian Journal of Pharmaceutical Education and Research)
Background and Objectives: Huntington’s Disease (HD) is a rare neurodegenerative disorder marked by abnormal body movements, behavioral and psychiatric issues, and dementia. This inherited genetic disorder leads to cognitive dysfunction and abnormal movements known as chorea. The condition was first accurately described by George Huntington, an Ohio physician, in 1872. HD is a dominantly inherited illness that causes progressive neurodegeneration in the striatum and other brain regions, particularly the cerebral cortex. This fatal condition is caused by an abnormally expanded and unstable cytosine-adenine-guanine repeat in the gene encoding the huntingtin protein. Materials and Methods: This review was conducted through a systematic and comprehensive literature search focused on animal models and pathophysiological mechanisms involved in HD. Results: Various hypotheses have been proposed to explain the pathogenic pathways of mutant huntingtin-induced neuronal dysfunction and cell death, but none provide a definitive explanation, making it an ongoing area of study. HD encompassing such as molecular genetics, selective neuronal susceptibility, excitotoxicity, mitochondrial dysfunction, apoptosis, and transcriptional dysregulation. Recent studies have highlighted the role of oxidative stress in HD development. Although no specific medication can prevent disease progression, there are drugs available to help reduce chorea symptoms. Animal models are crucial for evaluating potential treatments, with various models available that mimic some or many symptoms of HD. Conclusion: The biology of neurodegenerative disorders is better understood because of animal models. These models replicate the histological lesions, primary symptoms, and various facets of a particular disease. Furthermore, genetic or transgenic animal models have received a lot of attention in recent years. As research advances, refining these models will be crucial for developing effective therapeutic strategies that bridge the gap between preclinical findings and clinical outcomes in humans.
Keywords: Huntington’s disease; Neurodegenerative disorder; Cognitive disorder; Motor disorder.